Pola Pembelajaran Kreatif Komunikatif untuk Meningkatkan Kemampuan Berbicara Bahasa Arab Siswa Kelas III MTs Nurussabah Batunyala - Hatta, Mohamad (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This research is based on the low Arabic speaking skills of students due to unengaging and uncommunicative teaching methods. The aim of this study is to improve the Arabic speaking skills of third-grade students at MTs Nurussabah Batunyala for the 2024/2025 academic year through creative and communicative learning patterns. This study uses the Classroom Action Research (CAR) method conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. Data collection techniques include observation, interviews, and speaking skill tests. The collected data were analyzed descriptively, both qualitatively and quantitatively. The results of the study indicate that creative and communicative learning patterns are effective in improving students' Arabic speaking skills. In the first cycle, there was a 15% increase in the average speaking skills score compared to before the action. In the second cycle, a further increase of 20% was achieved, demonstrating that the implemented method significantly improved the students' speaking skills. The conclusion of this study is that the application of creative and communicative learning patterns can enhance the Arabic speaking skills of third-grade students at MTs Nurussabah Batunyala.